Effect of antenatal group discussion on fear of childbirth among pregnant women in a Nigerian tertiary hospital - Eleke, Chinemerem; Steve-Tamuno, Ogochukwu Francisca; Agu, Ifeyinwa S.; Ngbala-Okpabi, Sabinah O.; Samuel, Joy C. (International Journal of Research in Medical Sciences, 2023)
Background: Antenatal group discussions (AGDs) are utilized in antenatal peer support. Its application in controlling fear of childbirth (FOC) has not been widely studied in Africa. We examined the effect of AGDs on FOC among pregnant women. Methods: This experiment was done between in 2020 at a teaching hospital in Nigeria. We randomly assigned 218 consenting primigravid women into treatment (n = 111) and control groups (n = 107) and followed them from 31 to 38 weeks of gestation. The treatment group had one AGD session per week for 6 weeks, with each session lasting 120 minutes. The control group had no AGDs. The FOC Questionnaire was used for collecting data at 31 and 38 weeks of gestation. Inferential statistics were used for data analyses at a 5% significance level using SPSS 21. Results: At 31 weeks of pregnancy, 80.2% and 72.9% of participants in the treatment and control groups had unhealthy FOC (range 5 - 9) with no significant difference between the groups (p = 0.204). At 38 weeks, FOC was significantly less in the treatment group compared to the control group (17.1% vs. 48.6%, p<0.001). The AGD reduced the likelihood of unhealthy FOC by 65.0% (RR: 0.35, 95%CI: 0.22 - 0.55). Conclusions: Participation in AGDs reduced FOC among pregnant women, hence recommended. The current caesarean statistics may further reduce if pregnant women were encouraged to utilize AGDs.